Samp1, a RanGTP binding transmembrane protein in the inner nuclear membrane. (3rd July 2016) - Vijayaraghavan, Balaje; Jafferali, Mohammed Hakim; Figueroa, Ricardo A.; Hallberg, Einar
ABSTRACT: Samp1 is a transmembrane protein of the inner nuclear membrane (INM), which interacts with the nuclear lamina and the Linker of Nucleoskeleton and Cytoskeleton (LINC) complex in interphase and during mitosis, it localizes to the mitotic spindle. Samp1 was recently found to coprecipitate a protein complex containing Ran, a GTPase with fundamental regulatory functions both in interphase and in mitosis. To investigate the interaction between Samp1 and Ran in further detail, we have designed and expressed recombinant fusion proteins of the Chaetomium thermophilum homolog of Samp1 ( Ct .Samp1) and human Ran. Pulldown experiments show that Samp1 binds directly to Ran and that Samp1 binds better to RanGTP compared to RanGDP. Samp1 also preferred RanGTP over RanGDP in living tsBN2 cells. We also show that the Ran binding domain is located between amino acids 75–135 in the nucleoplasmically exposed N-terminal tail of Samp1. This domain is unique for Samp1, without homology in any other proteins in fungi or metazoa. Samp1 is the first known transmembrane protein that binds to Ran and could provide a unique local binding site for RanGTP in the INM. Samp1 overexpression resulted in increased Ran concentrations in the nuclear periphery supporting this idea.